Pra-Pelaksana Program Bantuan Stimulan Perumahan Swadaya (BSPS) Kelurahan Belawan Bahari Kecamatan Medan Belawan - Rafa Rafsanzani; Fajar Utama Ritonga (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2024)
The program to improve the quality of houses from uninhabitable houses to habitable houses is very beneficial for people who have uninhabitable houses. The quality of residential premises is one of the supporting indicators for improving community welfare. The quality of residential premises will refer to the quality of people's lives in the future. The government will strive to provide all forms of programs that refer to improving the quality of life of Indonesian people.. The program to improve the quality of self-help housing through the Self-Help Housing Stimulant Assistance (BSPS) program is an effort by the Ministry of Public Works, Public Housing (PUPR) to improve community welfare. Self-Help Housing Stimulant Assistance (BSPS) is government financial support for low-income communities to improve the quality of self-help housing. Implementation of the BSPS program in Belawan Bahari Village, Medan Belawan District requires several stages of activities. The pre-program implementation stage is the initial and preparatory stage before implementing the program. The program implementation method used is the Community Organization Community Development (COCD) method where aid recipients are united in the form of a community to proceed to the next stage.